Guru di Era Generasi Alpha: Studi Kasus Pada SD Negeri 87 Palembang - Nanda Saputra; Edi Harapan; Muhammad Fahmi (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of digital technology has given rise to Generation Alpha, a generation familiar from birth with gadgets, the internet, and a fast-paced and practical environment. This situation requires teachers to adapt to the mindsets, learning styles, and needs of students to ensure learning remains relevant and effective. This study aims to describe the roles, strategies, and challenges of teachers in dealing with Generation Alpha at Public Elementary School 87 Palembang. The research method used was a qualitative case study approach, through observation, interviews, and documentation. The results indicate that teachers are required to be more creative, innovative, and technologically literate in delivering material, while simultaneously building student character through interactive and collaborative learning. The main challenge faced by teachers is maintaining a balance between the use of technology and the development of discipline, empathy, and ethics in students. Thus, the role of teachers in the Generation Alpha era is not only as transmitters of knowledge, but also as facilitators, motivators, and role models in building the competencies and character of the future generation.